2007
DOI: 10.1348/026151007x185329
|View full text |Cite
|
Sign up to set email alerts
|

Fine motor skills and mathematics achievement in East Asian American and European American kindergartners and first graders

Abstract: This study examined whether fine motor skills were related to the initial scores and growth rate of mathematics achievement in American kindergartners and first graders. Participants were 244 East Asian American and 9,816 European American children from the US‐based Early Childhood Longitudinal Study (ECLS‐K). To control sampling bias, two subsamples of European Americans were matched to the East Asian American sample by socio‐economic status or fine motor skills, using propensity score matching. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 62 publications
7
106
0
9
Order By: Relevance
“…On the one hand, it can be concluded that the majority of these motor skills were related to mathematical scores. These findings are in line with the literature stressing the relationship between motor skills and mathematics in general (Luo, Jose, Huntsinger, & Pigott, 2007;Pagani et al, 2010). On the other hand, we found evidence that it is important to differentiate between different domains in mathematics as both visual perception as well as some motor domains do not contribute to both number fact retrieval and procedural calculation.…”
Section: Are Visual Perception Motor Skills and Visual-motor Integrasupporting
confidence: 92%
“…On the one hand, it can be concluded that the majority of these motor skills were related to mathematical scores. These findings are in line with the literature stressing the relationship between motor skills and mathematics in general (Luo, Jose, Huntsinger, & Pigott, 2007;Pagani et al, 2010). On the other hand, we found evidence that it is important to differentiate between different domains in mathematics as both visual perception as well as some motor domains do not contribute to both number fact retrieval and procedural calculation.…”
Section: Are Visual Perception Motor Skills and Visual-motor Integrasupporting
confidence: 92%
“…The FMS tests were taken from a battery designed to provide an estimate of children's FMS in preschool. Here we selected the three tasks that closely adhered to our definition of FMS as being meaningful and directed small muscle movements of the hand and excluded tapping and visuo-motor integration tasks (Luo et al, 2007). A further reason for selecting these tasks was that they constitute a unitary factor that exhibited, in comparison to tapping (see also Brookman et al, 2013) and broader manual control measures, stronger relations with WISC (Wechsler Intelligence Scale for Children) reasoning tasks in preschool children (Martzog et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…An old idea is that children's learning is shaped and enhanced by engaging in finely controlled motor activities, which comes to the fore in the saying 'nimble hands make for nimble minds' and in educational philosophies from the likes of Maria Montessori (Luo et al, 2007). The term embodied cognition is used to explain the long-standing idea that movement is key for learning (Barsalou, 2010) and such theories potentially provide an evidential and theoretical basis for studying links between FMS and cognitive development.…”
Section: Embodied Cognition and Links Between Vocabulary And Fine Motmentioning
confidence: 99%
“…Several empirical studies highlight the intriguing role that fine motor skills (FMS) play not just in cognitive and mathematical development (Grissmer, Grimm, Aiyer, Murrah, & Steele, 2010;Luo, Jose, Huntsinger, & Pigott, 2007;Pagani, Fitzpatrick, Archambault, & Janosz, 2010) are not simply accounted for by maturation. The need to account for maturation is further stressed by neurological theories, whereby certain neural regions may be implicated in both FMS and reading development (James & Gauthier, 2006).…”
Section: Introductionmentioning
confidence: 99%